Phosphinoyl radical-initiated vicinal hydroxy-phosphorylation of alkenes. Issue 47 (22nd November 2019) - Shoberu, Adedamola; Li, Shuai-Shuai; Zhang, Guo-Yu; Li, Da-Peng; Zou, Jian-Ping
Abstract: A protocol of Mn(OAc)3 –mediated α, β -hydroxy-phosphorylation of alkenes with phosphorus-centered radicals generated from diphenylphosphine oxide is described. A combination of steric and electronic factors played an important role in this reaction. The reactions of styrenes bearing ortho -substituent gave the selective β -hydroxyphosphine oxide products. Graphical abstract: Image 1 Highlights: The reactions of styrenes bearing ortho -substituent gave the selective β -hydroxyphosphine oxide products via a radical passway. A combination of steric and electronic factors played an important role in this reaction.